Design of Assesment Information System Employee Service in PT. Aerotrans Services Indonesia with Methods Key Performance Indicator (KPI) - Hidayat, Rachmat; Haryanto, Haryanto; Pramono, Yacob Agung (REMIK: Riset dan E-Jurnal Manajemen Informatika Komputer, 2019)
PT Aerotrans Services Indonesia employee appraisal data is processed conventionally by means of the Human Capital Business & Support print data points whose assessments must be filled out by their respective division heads, where after being printed the data is delivered to each division to be filled by each division supervisor then documents that have been filled in and signed by their respective division supervisors and returned by the Human Capital Business & Support division to be recorded. The objectives are to produce annual appraisal data for each employee and division, and there are company assessments made by VP Human Capital Business & Support and approved by the director is also still done conventionally. Even though the management has been organized, this method is still not optimal because in addition to requiring a long time and there are still operating paper documents, this method also has many weaknesses. The purpose of this research is to be able to build an information system that can be utilized by PT Aerotrans Services Indonesia to help process employee and company assessment data easily, quickly and accurately.